The Future of Oral Oncology: How Artificial Intelligence is Redefining Surgical Procedures and Patient Management - Marwan Al-Raeei (International Dental Journal)
Introduction and Aims: The future of oral oncology is significantly influenced by the incorporation of artificial intelligence (AI) technologies, such as surgical robotics and early histopathological diagnosis and detection of diseases. This article aims to explore the transformative effects of AI on the identification and diagnosis of oral cancer, emphasising the potential improvements in patient outcomes and the effectiveness of treatment options. Methods: An overview of the integration of AI technologies in surgical robotics and remote monitoring systems was conducted. This included an examination of AI algorithms used in surgical procedures for oral cancer, as well as the functionalities of AI-powered remote monitoring tools in disease management and patient care. Results: The application of AI in surgical robotics has led to increased precision and accuracy in oral cancer procedures, resulting in significantly improved patient outcomes with fewer complications. Furthermore, AI-driven remote monitoring systems facilitated personalised care and timely medical interventions, which contributed to better disease management. Notable positive results observed include decreased procedure durations, reduced complications, and accelerated recovery times for patients. Conclusion: The integration of AI technologies in oral oncology care has demonstrated significant potential for enhancing the quality of care, improving treatment outcomes, and streamlining clinical workflows. By leveraging AI, healthcare professionals can offer tailored treatment plans and improve long-term disease management for patients with oral cancer. Clinical Relevance: The implementation of AI in oral oncology represents an innovative approach to early detection and efficient management of oral cancer, ultimately enhancing the quality of life of the affected individuals. The findings underscore the importance of continuing to explore and adopt AI technologies to further advance healthcare delivery in oncology.